Anxiety Disorder in Drama The Peach Seasons (2007) by Debra Oswald - H L, Ratu Rejung; Rozani, An Fauzia (English Language and Literature, 2021)
This thesis is an analysis of the Drama The Peach Seasons (2007) by Debra Oswald. The purpose of this analysis is to expose the issue of anxiety disorder that refers to the protagonist who is a mother toward her daughter. This analysis is also intended to expose how the contribution of fictional elements (character and action/plot) in revealing the form of anxiety disorder. This analysis is related to the concept of psychoanalysis by Sigmund Freud. The result of this analysis shows the protagonist has anxiety disorder toward her daughter through the negative behaviour and irrational thinking.